2001
DOI: 10.4049/jimmunol.166.7.4743
|View full text |Cite
|
Sign up to set email alerts
|

Nonphlogistic Clearance of Late Apoptotic Neutrophils by Macrophages: Efficient Phagocytosis Independent of β2 Integrins

Abstract: Neutrophils undergo constitutive death by apoptosis, leading to safe nonphlogistic phagocytosis and clearance by macrophages. Recent work has shown that before secondary necrosis, neutrophils exhibiting classical features of apoptosis can progress to a morphologically defined late apoptotic state. However, whether such neutrophils could be safely cleared was unknown. We now report that human late apoptotic neutrophils could be purified from cultured neutrophil populations undergoing constitutive death and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 44 publications
5
68
2
Order By: Relevance
“…7). These results are in keeping with the earlier observations of Ren and Savill, who observed that apoptotic neutrophils beginning to become permeable to trypan blue were not proinflammatory (14). The response to lysed cells in the unstimulated macrophages was expected (2) in that they induced TNF-␣ and chemokine production; however, the levels were low relative to those seen with a strong proinflammatory stimulus such as zymosan or LPS (the latter not shown).…”
Section: Discussionsupporting
confidence: 76%
“…7). These results are in keeping with the earlier observations of Ren and Savill, who observed that apoptotic neutrophils beginning to become permeable to trypan blue were not proinflammatory (14). The response to lysed cells in the unstimulated macrophages was expected (2) in that they induced TNF-␣ and chemokine production; however, the levels were low relative to those seen with a strong proinflammatory stimulus such as zymosan or LPS (the latter not shown).…”
Section: Discussionsupporting
confidence: 76%
“…Phagocytosis of apoptotic neutrophils induced macrophages to secrete antiinflammatory cytokines and actively inhibited the production of proinflammatory cytokines (46). Similarly, late apoptotic neutrophils ingested by macrophages did not trigger the release of proinflammatory cytokines (47), whereas necrotic neutrophils induced macrophages to secrete inflammation mediators (48) and were able to efficiently costimulate T cells due to rapid up-regulation of CD40 (49). Clearly, these results and the results of the current study emphasize the differential effects of apoptotic and necrotic cells on macrophages and DCs and highlight the need for study of other types of primary cells.…”
Section: Discussionmentioning
confidence: 99%
“…25 Briefly, neutrophil suspensions were added to discontinuous Percoll gradients created by gently layering equal volumes of 31, 42 and 51% of a standard isotonic Percoll solution (90% Percoll þ 10% 10 Â phosphate-buffered saline (PBS)) in diluent (PBS) and centrifuged at 610 g for 28 min at 41C. The 0/31 and 42/51% Percoll interfaces contained the majority of necrotic, late and early apoptotic cells (490% were annexin-V-positive cells or incorporated PI), whereas the viable cells were collected at the bottom.…”
Section: Preparation Of Human Leukocytesmentioning
confidence: 99%